Kepuasan Pelanggan Dalam Perdagangan O2O (Online-to-Offline): Perspektif Fresh Product Di Restoran Chinese Food Sarto Kenongo Purwodadi - Apriliana, Mekar Icha; Isa, Muzakar (JURNAL MANAJEMEN PENDIDIKAN, 2025)
CUSTOMER SATISFACTION IN O2O (ONLINE-TO-OFFLINE) TRADING: FRESH PRODUCT PERSPECTIVE AT SARTO KENONGO PURWODADI CHINESE FOOD RESTAURANTThe development of online-to-offline (O2O) commerce has provided convenience for customers to order food digitally while enjoying the service directly at the restaurant. This model is becoming increasingly relevant for businesses that sell fresh products, including the Chinese Food restaurant Sarto Kenongo Purwodadi, which faces high demands regarding freshness, quality, and service reliability. This study aims to analyze the influence of corporate image, customer expectations, perceived quality, perceived value, product risk, and online shopping risk on customer satisfaction in the context of O2O commerce at the restaurant. The approach used is a quantitative method thru online distribution of questionnaires to customers, with measurement using a 5-point Likert scale and data analysis performed using SmartPLS. The research results indicate that corporate image has a positive and significant impact on customer expectations, perceived value, and customer satisfaction. Perceived quality is also proven to have a significant impact on customer expectations, perceived value, and customer satisfaction. Additionally, customer expectations positively influence perceived value, and perceived value significantly impacts customer satisfaction. Meanwhile, product risk did not significantly affect customer satisfaction, but online shopping risk showed a positive and significant influence. These findings indicate that corporate image, service quality, and customer values and expectations are key factors shaping customer satisfaction in the O2O model. Therefore, restaurants need to improve product quality, service consistency, and strengthen brand image to ensure optimal customer experiences both online and offline.